Research on the growth ability of Saccharomyces cerevisiae MN2 in the medium containing different concentrations of NaCl and NH\(_4^+\) for applying in aquaculture - Dang, Thi Mai Anh; Nguyen, Thu Minh; Luong, Huong Thi Thu; Nguyen, Nguyen Sy; Ho, Cuong Tu (Vietnam Journal of Marine Science and Technology, 2023)
Salinity is one of the factors affecting the growth and activity of microorganisms. The study of the salinity effect can indicate the range of microorganism applications. This study evaluated the effects of NaCl concentration on growth, amino acid and NH4+ absorption of yeast strain Saccharomyces cerevisia MN2. The results showed that, within NaCl concentration from 0 to 3%, the negative effects on the growth of MN2 strain were not observed. The cell density on all culture media reached 108 CFU/ml after 24 hours and maintained until 48 hours.The strain NM2 was able to absorb amino acids at a high rate, which was indicated by the decrease of the amino acid concentration in the culture media after 48 hours (from 20.8 to 37.5%) in comparison with the control. In addition, the strain NM2 was also able to decrease NH4+ concentration in culture media, reducing from 17 to 25.4% in comparison with the control after 48 hours. Strain MN2 is capable of using ammonium as a nitrogen source. When the ammonium concentration fluctuated in the range of 37,327 - 75,433 mg/l, it did not affect the growth of MN2 much. In conclusion, the strain of S. cerevisia MN2 is tolerance to the salinity up to 3%, and suitable for the aquaculture wastewater treatment process.